(3eUjHI TjN GdESdGe GHf JjejIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3Ydi Hf MSf Hf eMeO GdMQGfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi cd MGd gPG SDGd CHj GdbGSe jhSa Hf eMeO Hf Ydi GdSHJi YaG Gddg Yfg HJaVd SjOfG CMeO Hf JjejI Cf jhUfi s
(3BNQgG (B:s
(3GdMeO ddg QH GdYGdejfq s
(3Vef eLehY , JQJjHgG (B: 2s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs